CRYPTOGRAPHY PASSWORD IN WEB APPLICATIONS USING MD5 ALGORITHM - Mochammad Sofyan Arief; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2005)
Cryptography is the art and science of hiding information from recipients who did notberhak.Dalam paper discusses about related cryptographic dengankerahasianpassword is a one-way functions, hash functions, and key derivation functions.MD5 Crypt is one of the key derivation functions that process the input stringpassword and salt using MD5 algorithm loop to produce output. If the input string thelonger the password, then the time required to produce the output of MD5 cryptlonger.